Analisis Strategi Pemasaran Dalam Meningkatkan Penjualan: (Studi Kasus Outlet Smartphone Samsung di Mall Boemi Kedaton) - Christian Edbert; Habiburahman Habiburahman (Jurnal Widya, 2023)
This study aims to determine the best marketing approach to increase Samsung smartphone store sales. A SWOT analysis is carried out to assess the situation. Based on the conversation, the Cartesian SWOT chart shows that an aggressive growth policy is the strategy used in this situation (growth-oriented strategy), which refers to the industrial world where there is a market leader and the next order is called . applicant A market challenger is a company that is constantly and openly trying to increase its market share.